KONSTRUKSI SOSIAL BAU NYALE PADA MASYARAKAT LOMBOK - Pena, Eko Nuari; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study aims to investigate and explain how the influence of the bau nyale tradition on the Lombok society. The approach used in this study was descriptive exploratory research and uses social construction theory analysis from Peter L. Berger. Based on the results of the field research, it is found the influence of the bau nyale tradition on the structure and behavior patterns of Lombok society which was influenced by myths, folklore or legend about Princess Mandalika who was willing to sacrifice herself for peace and transform into nyale, which resulted the construction or assumption in Lombok society that nyale is a blessing and prosperity for anyone who comes to catch it. Thus, in this case, the government also helped shape the construction of the bau nyale through reproduction of discourse, festivals, parades, and government projects in order to preserve tradition .   Keywords: Bau Nyale, Lombok Society, Social Construction, Tradition.